DNA metabarcoding reveals ecological patterns and driving mechanisms of archaeal, bacterial, and eukaryotic communities in sediments of the Sansha Yongle Blue Hole - Qingxia Li; Yanli Lei; Tiegang Li (Scientific Reports, 2024)
Abstract The Sansha Yongle Blue Hole (SYBH) is the world’s deepest marine blue hole with unique physicochemical characteristics. However, our knowledge of the biodiversity and community structure in SYBH sediments remains limited, as past studies have mostly focused on microbial communities in the water column. Here, we collected sediment samples from the aerobic zone (3.1 to 38.6 m) and the deep anaerobic zone (150 m, 300 m) of the SYBH and extracted DNA to characterize the archaeal, bacterial, and eukaryotic communities inhabiting these sediments. Our results showed that the archaeal and bacterial communities were dominated by Thaumarchaeota and Proteobacteria, respectively. The dominant taxa of eukaryotes in different sites varied greatly, mainly including Phaeophyceae, Annelida, Diatomea and Arthropoda. All three examined domains showed clear vertical distributions and significant differences in community composition between the aerobic and anaerobic zones. Sulfide played a prominent role in structuring the three domains, followed by salinity, nitrous oxide, pH, temperature and dissolved oxygen, all of which were positively correlated with the turnover component, the main contributor to beta diversity. Neutral community model revealed that stochastic processes contributed to more than half of the community variations across the three domains. Co-occurrence network showed an equal number of positive and negative interactions in the archaeal network, while positive interactions accounted for ~ 80% in the bacterial and eukaryotic networks. Our findings reveal the ecological features of prokaryotes and eukaryotes in SYBH sediments and shed new light on community dynamics and survival strategies in the special environment of marine blue holes.